Implementasi aplikasi m-health model psikoedukasi dalam peningkatan pengetahuan dan kepatuhan minum obat pada pasien tuberkulosis paru - Dewi Fitriani; Gilang Rahmatulloh; Firman Yudiatma; Asep Fiqri Hidayat (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Many Patient Pulmonary TB sufferers don’t comply with treatment because they feel bored. Pulmonary TB treatment lasts quite a long time so that many sufferers drop out of treatment and experience psychological problems. The importance of strategies and efforts to increase knowledge and compliance with the use of technology. Purpose: To analyze the differences in the implementation of the psychoeducational model m-health application in improving knowledge and compliance in taking medication in pulmonary tuberculosis patients. Method: The research was carried out using a quantitative approach, with a true experimental research design using two control groups with the provision of psychoeducation. Intervention group by providing psychoeducational m-health applications. The total sample size was 140 participants, with details of 70 in the control group and 70 participants in the intervention group at the South Tangerang regional health center. Results: The majority of participants' education was junior high school-high school graduates, in the control group there were 49 participants (70%) and the intervention group there were 46 participants (65.7%). Based on statistical tests, there were differences in the level of knowledge and compliance of the control and intervention groups with a p-value of 0.000 <0.05. Conclusion: There is a difference between the intervention group and the control group. The intervention group using the m-health application of the psychoeducational model has a better level of knowledge and compliance than the control group because it uses the m-health application. Keywords: Application; Compliance; Knowledge; Psychoeducation; Pulmonary Tuberculosis. Pendahuluan: Banyak penderita tuberculosis (TB) paru yang tidak patuh terhadap pengobatan karena merasa jenuh. Pengobatan TB paru berlangsung cukup lama sehingga banyak penderita yang putus berobat dan mengalami masalah psikologi. Pentingnya strategi dan upaya dengan peningkatan pengetahuan dan kepatuhan dengan pemanfaatan teknologi. Tujuan: Untuk menganalisis perbedaan implementasi aplikasi m-health model psikoedukasi dalam peningkatan pengetahuan dan kepatuhan minum obat pasien tuberculosis paru. Metode: Penelitian kuantitatif dengan desain true eksperiment menggunakan dua kelompok kontrol pemberian psikoedukasi. Kelompok intervensi dengan pemberian Aplikasi m-health psikoedukasi. Total jumlah sampel 140 partisipan, dengan rincian 70 kelompok kontrol dan 70 partisipan pada kelompok intervensi pada puskesmas wilayah Tangerang Selatan. Hasil: Mayoritas pendidikan partisipan adalah lulusan SMP-SMA, pada kelompok kontrol adalah 49 partisipan (70%) dan kelompok intervensi sebanyak 46 partisipan (65.7%). Berdasarkan uji statistik, terdapat perbedaan tingkat pengetahuan dan kepatuhan kelompok kontrol dan intervensi dengan p-value 0.000 <0.05. Simpulan: Terdapat perbedaan antara kelompok intervensi dan kelompok kontrol. Kelompok intervensi dengan menggunakan aplikasi m-health model psikoedukasi memiliki tingkat pengetahuan dan kepatuhan yang lebih baik daripada kelompok kontrol. Kata Kunci: Aplikasi; Kepatuhan; Pengetahuan; Psikoedukasi; Tuberculosis Paru.